Mithramycin targets head and neck cancer stem cells by inhibiting Sp1 and UFMylation - Kristina Vukovic Derfi; Tea Vasiljevic; Tea Dragicevic; Tanja Matijevic Glavan (Cancer Cell International)
Abstract Background The development of resistance to therapy is characteristic of head and neck squamous cell carcinoma (HNSCC), the 6th most common cancer, and is often attributed to cancer stem cells (CSCs). By proteomic approach, we determined that UFMylation plays an important role in HNSCC CSCs. Because of the necessity for innovative therapeutic strategies, we explore here the therapy targeting CSCs based on mithramycin and its inhibitory effect on Sp1 transcription factor, UFMylation, and CSCs survival and stemness. Methods HNSCC-derived cancer cell lines Detroit 562, FaDu, and Cal27, and tumor spheres are used as a model for CSCs. Proteomic analysis identified the importance of the UFMylation pathway in CSCs which we further studied by bioinformatics, western blot, immunocytochemistry, and cytotoxicity assay. Results Proteomic analysis and subsequent confirmation revealed UFSP2 and DDRGK1 were strongly expressed in tumor spheres. Bioinformatic analysis indicated high expression of UFM1 is linked with worse overall and disease-free survival, and it correlated with main EMT proteins (Zeb, Twist, and Fn) in HNSCC. UFM1 was also strongly expressed in tumor spheres compared to the adherent cells. Silencing of UFM1 reduced sphere number, size, and stemness. As Sp1 is the main transcription factor for the genes of the UFMylation system, we explored its inhibitor mithramycin, as a potential drug for CSCs inhibition. We proved mithramycin inhibits CSCs survival, induces apoptosis, and reduces UFMylation and stemness. Conclusion UFMylation is an important process in CSCs, and mithramycin, or its lesser toxic analogs, should be further explored as CSCs targeted therapy in HNSCC.